Digital Literacy Training and Learning Innovation in the Digital Era at IGTKI Sub-districts throughout Medan City - Batubara, Beni Arbi (Abdimas Indonesian Journal, 2025)
This community service activity was carried out to strengthen the capacity and competence of teachers in facing the challenges of education in the digital era. The digitalization of education requires teachers to be able to adapt to developments in information and communication technology (ICT) and integrate it into the learning process creatively and effectively. This activity was carried out with teachers who are members of the Indonesian Kindergarten Teachers Association (IGTKI) in all sub-districts throughout Medan City. The implementation method was carried out through training, workshops, and intensive mentoring on digital literacy, the creation of interactive learning media, and the use of online learning platforms. The results of the activity showed a significant increase in teachers' understanding and skills in designing digital-based learning that is engaging, interactive, and contextual. Through this program, teachers are able to utilize technology as a means of strengthening creativity, collaboration, and communication in early childhood learning. Thus, this community service activity contributes to forming an educational ecosystem that is adaptive, innovative, and ready to face the digital transformation in the future.